Evaluasi Kinerja Penyediaan Air Bersih di Kelurahan Baru Ulu, Kecamatan Balikpapan Barat, Kota Balikpapan - Risa Andini; Mega Ulimaz; Sulistijono Sulistijono (P4W LPPM IPB, 2017)
Kelurahan Baru Ulu is a coastal area in Kecamatan Balikpapan Barat. This area is dominated by the settlement activities; therefore, it relies on high demand of clean water. However, the society’s need of clean water that lives in this area is not fulfilled completely. This research aims on evaluating the performance of supplying clean water in the mentioned area using the Importance Performance Analysis so that the result of this research will be the main indicator in fulfilling clean water supply at Kelurahan Baru Ulu. According to the analysis, the indicators of clean water supply which has the high importance followed by the low performance are the bacterial substance, saltiness, smell in the water, water discharge, amount of water from the source, duration of water flowing per day, water supply in the morning, and residents’ agreement on water tariff.